Oxymatrine and Cisplatin Synergistically Enhance Anti-tumor Immunity of CD8+ T Cells in Non-small Cell Lung Cancer - Ye, Jin; Zou, Man-Man; Li, Pei; Lin, Xi-Jun; Jiang, Qi-Wei; Yang, Yang; Huang, Jia-Rong; Yuan, Meng-Ling; Xing, Zi-Hao; Wei, Meng-Ning; Li, Yao; Shi, Zhi; et al. (Frontiers in Oncology, 2018)
Oxymatrine (OMT) has shown broad antitumor activities for the treatment of several types of cancers. However, little is known about its effect on anti-tumor immunity. Combination therapy is a potentially promising strategy of cancer to enhance anticancer activity, overcome drug resistance, and lower treatment failure rate. In the present study, we demonstrated that the combination of OMT with cisplatin (DDP) synergistically inhibited non-small cell lung cancer (NSCLC) cells growth when co-cultured with peripheral blood mononuclear cells in vitro. Furthermore, the combination of OMT with DDP significantly inhibited the growth of Lewis lung cancer (LLC) mouse xenograft tumors. Flow cytometry analysis revealed that OMT and DDP synergistically increase the CD8+/ regulatory T cells ratio and enhanced more CD8+ T cells secreted cytokines of IFN-γ, TNF-α and IL-2 in vivo. Mechanistically, upregulation of miR-155 and downregulation of suppressor of cytokine signaling-1 (SOCS1) were confirmed as a target signaling pathway to positively regulate the anti-tumor response of CD8+ T cells. Overall, OMT in combination with DDP showed outstanding synergistic anti-tumor immunity, suggesting that this beneficial combination may offer a potential immunotherapy for NSCLC patients.